Treatment of the most common respiratory infections in children - Basa, Mihail; Sovtić, Aleksandar (Archives of Pharmacy, 2022)
Acute respiratory infections are the most common group of infective diseases in the pediatric population. Although the improvement of health care and vaccination program has led to a significant reduction in the incidence of certain respiratory infections, the combination of a high prevalence in vulnerable pediatric categories and uncritical prescription of antibiotics, due to the inability to adequately distinguish between viruses and bacterial etiology, still represents a significant challenge for the public health system. In order to promote rational antibiotic therapy with an overall improvement of both diagnostic and therapeutic principles, acute respiratory diseases have been the subject of consideration in numerous publications and national guidelines. Nonspecific clinical manifestations with pathogen heterogeneity and both anatomical and physiological characteristics of the child’s respiratory system during growth and development have created the need for individualized therapy. Since the guidelines emphasize the undoubtful and crucial benefits of symptomatic therapy (e.g. analgesics in acute otitis media, supplemental oxygen in lower respiratory tract infections with hypoxemia), the use of antibiotics and corticosteroids is indicated in selected cases with a severe clinical picture. The choice of antibiotic depends on the clinical condition, presumed causative agent, and local epidemiologic circumstances. Respiratory support (oxygen therapy and/or artificial ventilation) is reserved for inpatient treatment of cases with a particularly severe clinical picture and associated complications.